Assessment of the Feeding Practices in Infants and Young Children and its Association with Nutritional Status in Urban Areas - Naik, Aneesha Rajaram; Patil, Sanjivani Vishwanath (International Journal of Child Health and Nutrition, 2023)
Background: Poor nutrition at an early age leads to malnutrition, which in turn leads to an increase in risks of repeated infections, which is responsible for the poor health of children. The nutritional status of a child is directly proportional to their feeding practices, which are dependent on the knowledge and practices followed by the mother. This study assesses the level of knowledge and practices among mothers on feeding practices for their infants and young children and its association with nutritional status. Methods and Materials: A cross-sectional study was conducted in the households of urban slums in the field practice area of the Urban Health Training Centre of a private medical college. A questionnaire consisting of sociodemographic data, knowledge of breastfeeding, knowledge of complementary feeding, and actual practices of feeding the children from 0 –2 years was used for data collection using Google Forms, followed by anthropometric measurements of the children with the help of WHO standardized growth charts to assess their nutritional status. Results: Out of 112 participants, 37.5% of the mothers were less than 25 years old. The mean age of the babies was found to be 11 + 6.49 months. 53.57% of mothers had good knowledge, and 72.32% of mothers followed correct feeding practices. Conclusion: There is a significant association of good knowledge among mothers with babies who did not show wasting. There is no association between knowledge and feeding practices being followed.